DNA methylation variation is crucial to restore adventitious rooting ability during in vitro shoot culture‐induced rejuvenation in apple rootstock. (13th March 2023) - Wang, Zhe; Li, Zhengnan; Wu, Dongchen; Tian, Qiuye; Su, Shenghui; Cheng, Chenxia; Nie, Jiyun; Yuan, Yongbing; Wang, Yongzhang; Xu, Xiaozhao
SUMMARY: In vitro shoot culture has been widely used for restoring adventitious rooting ability in rooting recalcitrant woody perennial species for the past few decades, but its molecular mechanism is largely uncovered. DNA methylation is an essential epigenetic mark that participates in many biological processes. Recent reports suggested a role of DNA methylation in vitro culture in plants. In this study, we characterized the single‐base resolution DNA methylome and transcriptome of adult and in vitro shoot culture‐induced rejuvenation cuttings of apple rootstock M9T337. We found a global decrease in DNA methylation during rejuvenation, which may be correlated with increased expression of DNA demethylase genes and decreased expression of DNA methyltransferase genes. We additionally documented DNA hypomethylation in 'T337'_R in gene protomer associated with higher transcript levels of several adventitious rooting‐related genes. The application of a DNA methylation inhibitor (5‐azacytidine) enhanced the adventitious rooting ability and the expression level of adventitious rooting‐related genes, such as, MdANT, MdMPK3, MdABCB21, MdCDC48, MdKIN8B, pri‐MdMIR156a5 and pri‐MdMIR156a12 . Together, the DNA hypomethylation is critical for the rejuvenation‐dependent adventitious rooting ability in apple rootstock. In addition, increased DNA methylation was also found in thousands of genes in 'T337'_R. We additionally documented that DNA hypermethylation is required for inhibition of adventitious rooting‐repressed genes, such as MdGAD5a, encoding glutamate decarboxylase, which can catalyze glutamate decarboxylated to form γ‐aminobutyric acid (GABA). Our results revealed that in vitro shoot culture‐dependent DNA methylation variation plays important roles in adventitious rooting in apple rootstock. Significance Statement: In vitro shoot culture has been widely used for restoring adventitious rooting ability in rooting recalcitrant woody perennial species for the past few decades, but its molecular mechanism is largely uncovered. We revealed critical roles of DNA demethylation in the activation of adventitious rooting‐induced genes and DNA methylation in inhibition of adventitious rooting‐repressed genes in rejuvenated cuttings of apple rootstock 'T337'.